Realization of desktop 3D printer through micromachined active pump matrix - Gong, Thomas Haiqing. (2008)
In rapid prototyping, one of the feasible methods of achieving fast and low cost forming of 3D physical objects is by 3D printer. The main issues of the present 3D printer are the high cost and poor resolution of the printer head due to its complex fabrication and assembly processes. MicroElectroMechanical Systems (MEMS) technology was seen to be the solution to overcome those limitations. The motivation of this research is thus to design and develop high performance liquid dispenser (either single or array) based on MEMS technology for addressing the above issues. Because of the growing need for high performance liquid dispensers with high operating speed (operating frequency > 5kHz), piezoelectric driven membrane actuators for the dispensers are a favorable design.